Implementing a systems approach to suicide prevention in a mental health service using the Zero Suicide Framework. (March 2021) - Turner, Kathryn; Sveticic, Jerneja; Almeida-Crasto, Alice; Gaee-Atefi, Taralina; Green, Vicki; Grice, Diana; Kelly, Petra; Krishnaiah, Ravikumar; Lindsay, Luke; Mayahle, Brian; Patist, Carla; Van Engelen, Heidy; et al.
Objective: The Zero Suicide Framework, a systems approach to suicide prevention within a health service, is being implemented across a number of states in Australia, and internationally, although there is limited published evidence for its effectiveness. This paper aims to provide a description of the implementation process within a large health service in Australia and describes some of the outcomes to date and learnings from this process. Method: Gold Coast Mental Health and Specialist Services has undertaken an implementation of the Zero Suicide Framework commencing in late 2015, aiming for high fidelity to the seven key elements. This paper describes the practical steps undertaken by the service, the new practices embedded, emphasis on supporting staff following the principles of restorative just culture and the development of an evaluation framework to support a continuous quality improvement approach. Results: Improvements have been demonstrated in terms of processes implementation, enhanced staff skills and confidence, positive cultural change and innovations in areas such as the use of machine learning for identification of suicide presentations. A change to 'business as usual' has benefited thousands of consumers since the implementation of a Suicide Prevention Pathway in late 2016 and achieved reductions in rates of repeated suicide attempts and deaths by suicide in Gold Coast Mental Health and Specialist Services consumers. Conclusion: An all-of-service, systems approach to suicide prevention with a strong focus on cultural shifts and aspirational goals can be successfully implemented within a mental health service with only modest additional resources when supported by engaged leadership across the organisation. A continuous quality improvement approach is vital in the relentless pursuit of zero suicides in healthcare.